Spiritualitas Persaudaraan Universal: Belajar dari Kisah Orang Samaria yang Baik Hati (Lukas 10:25-37) - Kristiyanto, Nikolas (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2023)
Humans can never live alone, but they will always need other people in their lives. Human philosophy calls this intersubjectivity. Humans are always part of a larger community than just themselves. It is not surprising that Aristotle said that humans cannot live in isolation. From here, Christian ethics guides us that respecting others is part of our faith and that our fellow human beings are equal creations of God – not limited by any criteria created by humans. However, Jesus demanded more from His followers. Not only to understand "who is a neighbour", but Jesus wanted His followers to "be a neighbour" to others, even to "enemies". From this, the so-called "Spirituality of Universal Brotherhood" was born, where this "Spirituality of Universal Brotherhood" is ultimately not just a mere "concept", but a "common project" that is constantly lived and never ends in this life to realise a harmonious, peaceful, and salvific common life for everyone.